RETRACTED: OTUB2 Facilitates Tumorigenesis of Gastric Cancer Through Promoting KDM1A-Mediated Stem Cell-Like Properties - Liu, Guangming; Guo, Wei; Qin, Junjie; Lin, Zhiliang (Frontiers in Oncology, 2021)
Otubain 2 (OTUB2), a deubiquitinating enzyme, overexpression is considered to predict poor outcome in various cancers. However, the function and potential regulatory mechanisms of OTUB2 in gastric cancer (GC) progression remains unclear. To determine how OTUB2 participate in GC progression, the gain and loss of-function experiments were conducted in vivo and in vitro. We found that OTUB2 was upregulated in GC samples (n=140) and cells. Moreover, the overall, first progression and post progression survival rates of GC patients with high OTUB2 expression showed a poorer prognosis than that in those patients with low OTUB2 expression. Down-regulation of OTUB2 suppressed sphere formation and reduced expression of stem cell markers in GC cells. Furthermore, OTUB2-silenced GC cells also showed a decreased proliferation, invasion, migration, and in vivo tumorigenic ability. However, OTUB2 overexpression showed the opposite effects. Notably, we demonstrated that OTUB2 increased lysine-specific histone demethylase 1A (KDM1A) expression through deubiquitination. KDM1A, a demethylase known to promote demethylation of downstream genes, was identified to promote the maintenance of cancer stem cell characteristics. Moreover, the alterations caused by OTUB2 overexpression were partly inversed by KDM1A knockdown and in turn KDM1A overexpression reversed the changes induced by OTUB2 shRNA. Taken together, we demonstrate that OTUB2 may serve as a vital driver in GC tumorigenesis by enhancing KDM1A-mediated stem cell-like properties.